STATISTICAL ASSESSMENT OF THE NET CONTRIBUTION OF CLIMATE CHANGE TO THE FORMATION OF POLLUTANT CONCENTRATIONS IN THE ATMOSPHERIC AIR OVER THE TERRITORY OF UKRAINE - SAVENETS, Mykhailo; KRAINYK, Sofiia; HRAMA, Daria; RUDAS, Maryna; SKLIAR, Oksana (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. Air pollution and climate change are among the key factors of negative anthropogenic impact on the environment. The variability of pollutants largely depends on emissions; however, the role of climate change in shaping pollutant concentrations remains insufficiently studied. This aspect is crucial for long-term planning to improve air quality and develop emission reduction strategies. This study presents an analysis of the net contribution of climate change to the formation of harmful pollutant concentrations using a statistical approach to time series decomposition. Methods. The research is based on monthly emission and concentration data of nitrogen dioxide (NO2), formaldehyde (CH2O), and tropospheric (ground-level) ozone (O3) from the Copernicus Atmospheric Monitoring Service (CAMS) reanalysis for the period from 2003 to 2021, as well as air temperature, wind speed, and precipitation data from the ERA5 reanalysis. The application of an additive statistical model allowed the decomposition of pollutant concentrations’ time series into seasonal (intra-annual) components, interannual trends, and interannual dependencies of NO2, CH2O, and O3 variability on fluctuations of climate parameters. Results. Seasonal variability in pollutants’ concentrations, which depends both on meteorological changes and differences in pollutant emissions, explains 61–74% of the total variability of NO2 and about 90% of CH2O and O3. The interannual trends of the studied pollutants, which are influenced by changes in anthropogenic load, ranged from 0.6% to 3.6% for NO2 and are generally below 1% for CH2O and O3, yet with statistically significant changes. The net contribution of climate change, assessed through the statistical relationship between interannual variations of pollutant anomalies and anomalies in climate parameters, showed that climate change accounts for less than 10% of the total pollutants’ variability. On average, this contribution is approximately 5% for NO2, 3% for O3, and only about 1% for CH2O. Conclusions. The obtained results indicate that the development of air pollution reduction strategies and air quality improvement should primarily focus on reducing direct anthropogenic emissions and their negative impact on public health and ecosystems. However, the role of climate change should also be considered as a significant factor in the formation of atmospheric pollution.